An Analysis of Quality of Reading Literacy Skills of Students in Formal Primary Schools and Non-Formal Basic Schools - Javaria Hussain (IJLTP, 2025)
Literacy acquisition and enhancement is the core of all debates of multiple educational forums nationally and internationally. Primary level is considered most important for literacy skills development. Formal and non-formal institutes are playing their roles separately. Out of basic literacy skills, reading skill is an important area which was explored in this study. This was a comparative study on basic literacy skills (reading skills) of primary level learners from formal education and Non-formal Basic Education Schools (NFBES). The aim was to assess the quality of reading skills among students in both school systems and identify any significant differences in reading achievement. The researcher selected 100 students from both types of schools, 50 from each. Participants’ skill was assessed using a test designed to measure their reading ability. Findings indicate that while students from formal schools performed slightly better in reading, the gap in achievement between the two groups was not statistically significant. The results emphasize the need for targeted interventions to improve reading skills, particularly in non-formal school settings. The study highlights the role of teacher training and curriculum development in addressing literacy gaps.